Life's bulldozer moments : how adversity leads to success in life and business. - Tramuto, Donato (Hamilton Books, 2016)
A successful health care entrepreneur and global philanthropist, recounts the lessons he learned along the way and shows that adversity can lead to success in life and business. He shows anyone bulldozed by life how to pull themselves out of the rubble, dust themselves off and find meaning and purpose.